Ecuador : An Economic and Social Agenda in the New Millennium - Fretes-Cibils, Vicente; Giugale, Marcelo M.; López-Cálix, José Roberto (World Bank: Washington, DC, 2013)
The book focuses on three overarching themes: fiscal consolidation and growth; social development; and, quality of government, and, documents Ecuador's development trends, policies, and options. The fundamental challenges facing the country are identified within this book, and the solutions represent a break with the past: this is a proposal for an agenda with a broad, and integrated vision of economic, and social development in Ecuador. As a central message, the book outlines that although economic growth is a necessary condition to combat poverty, it would however be insufficient, unless growth is sustainable, and participatory, i.e., that broad sectors of the most vulnerable population (such as marginalized indigenous populations) are included. Thus, the argument for preserving stability with fiscal discipline, and accelerating growth with competitiveness, is based on a guaranteed balanced macroeconomic framework, that promotes economic expansion and competitiveness by making input markets - particularly the labor market - more flexible, by opening the economy to foreign trade, and eliminating trade policies. Expansion of the petroleum sector should be accelerated through legal and regulatory changes to prod fiscal stability, and promote private investments. Boosting sustainable, and equitable social development can be ensured by the government through actions focused on human capital development, improved quality of education and health services, and efficient social safety network. And in building a quality government that serves its people, and fights against corruption, the book stipulates regulatory reforms, and provision of direct services, within a strategy complemented with strengthened civil service, and deepening of the judicial reform, in the general context of decentralization.